(untitled) (Anclajes, 2021)
In 1950, Mexico arrived in Italy. During the XXV Venice Biennale, works of post-revolutionary Mexican art were exhibited for the first time in Europe, and since then they have circulated on the European continent through exhibitions and publications. In Italy in particular, the experiences of Mexican muralism were considered an indispensable model for many artists and intellectuals. Moreover, they are an inspiration for the emergence of a public art movement that expressed itself through the production of murals with a clear political content during the period between 1950 and 1980. This essay shows how muralism constitutes a field of fruitful exchange between the two contexts addressed, breaking the stereotype that has always seen the artistic relationship between Mexico and Italy in a unidirectional way with a Eurocentric gaze.